Electrochemical Performance of WS2-CNT Core–Shell Heterostructures for the Detection of Vitamin B2 - Rayhane Zribi; Muhammad Hamid Raza; Nicola Pinna; Giovanni Neri (Proceedings)
In this study, a novel electrochemical sensor was developed for the quantitative determination of riboflavin. The tungsten disulfide (WS2) layer was deposited on carbon nanotubes (CNTs) by atomic layer deposition (ALD), forming a CNTs-WS2 core–shell heterostructure. This material was used to modify the commercial screen-printed carbon electrode in order to enhance its electrocatalytic activity toward the detection of vitamin B2. Cyclic voltammetry was performed as a preliminary test in the presence of riboflavin. In addition to this, an extensive electrochemical study was performed using differential pulse voltammetry, demonstrating that modified the CNTs-WS2/SPCE sensor display superior electrochemical performance compared with bare SPCE. The sensor exhibits a linear response in the concentration range from 0 µM to 45 µM, with remarkably enhanced sensitivity (9 μAμM−1cm−2) compared with the bare electrode, with a limit of detection (LOD) of 1.24 µM. This enhancement is attributed to the conformal growth of the WS2 flakes on the CNTs and the high surface area offered by these flakes.